2011
DOI: 10.1038/bmt.2011.190
|View full text |Cite
|
Sign up to set email alerts
|

Differences in mothers’ and fathers’ health-related quality of life after pediatric SCT: a longitudinal study

Abstract: The purpose of this study was to examine longitudinally health-related quality of life (HRQOL) and related factors in mothers and fathers of children who undergo SCT, before, and 1 and 2 years after SCT. A total of 84 parents (49 mothers/35 fathers) of patients diagnosed mainly with leukemia completed a HRQOL measure before SCT, 46 at 1 year (26 mothers/20 fathers) and 50 parents (31 mothers/19 fathers) at 2 years post SCT. Physical and psychosocial HRQOL summary scores are reported. Parents' age and gender, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 27 publications
2
26
0
Order By: Relevance
“…Our overall sample size is robust and likely sufficient to permit detection of a significant difference if it existed. That being said, differences between mothers and fathers with regard to psychological distress and coping before HSCT have been described, and this issue warrants further study [16,49]. Second, the study sample was drawn in part from an intervention study, although the findings presented are from data collected occurred before randomization.…”
Section: Discussionmentioning
confidence: 99%
“…Our overall sample size is robust and likely sufficient to permit detection of a significant difference if it existed. That being said, differences between mothers and fathers with regard to psychological distress and coping before HSCT have been described, and this issue warrants further study [16,49]. Second, the study sample was drawn in part from an intervention study, although the findings presented are from data collected occurred before randomization.…”
Section: Discussionmentioning
confidence: 99%
“…Recent longitudinal studies have identified an association of additional baseline risk factors with the trajectory of HRQL following HCT, including child age (older, worse HRQL),[14, 19, 20] child gender (female, worse HRQL), [20] rater (mothers report lower HRQL than fathers; children report better HRQL than parents),[18, 21] concordance by primary language or by gender of the raters (concordant pairs, higher HRQL),[22] parental emotional distress, (greater distress, worse HRQL),[18, 23] and child race, (African American, better HRQL). [20] Larger studies are needed to confirm these findings in medically and demographically diverse samples.…”
Section: A Health-related Quality Of Lifementioning
confidence: 99%
“…HRQoL has been previously studied in caregivers of children with different diseases, including pediatric oncology populations . In most studies, caregivers reported significant impairment in both mental and physical HRQoL domains.…”
Section: Introductionmentioning
confidence: 99%
“…Identified risk factors were (among others) female parent gender, preexistent parental illness, lack of social or emotional support, less effective coping strategies, and child characteristics such as worse functional status, higher care dependency, and more symptoms or increased disease activity . In childhood oncology, additionally described risk factors are treatment intensity, shorter time since diagnosis, high parental distress and family burden, and lower socioeconomic status …”
Section: Introductionmentioning
confidence: 99%